Participación V Reunión de Antropología de la Ciencia y la Tecnología (V REACT ), 20 al 22 de mayo 2015, Porto Alegre, Brasil - Medina, Sebastián; Manrique, Diana; Mendonça, Maíra (Revista Chilena de Salud Pública, 2015)
: